2022
DOI: 10.1111/jgs.17669
|View full text |Cite
|
Sign up to set email alerts
|

Post‐acute care transitions and outcomes among medicare beneficiaries in assisted living communities

Abstract: Background Despite the rapid growth of assisted living (AL) and frequent hospitalizations among AL residents, little is known about their patterns of post‐acute care transitions and outcomes. This study examined the post‐acute care transitions among AL residents and their association with outcomes in the first 30 and 60 days after hospital discharge. Methods This study used data from 2018 national Medicare enrollment and claims datasets, the Minimum Data Set (MDS), and Medicare Provider Analysis and Review (Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(77 reference statements)
0
7
0
Order By: Relevance
“… 17 , 18 , 24 , 25 , 36 For some patients and families, professional supports were critical when caregiving at home was not an option. 11 , 26 , 29 Recently developed telemonitoring service might be a solution to the geographic disparities in access to home-based services. 18 , 27 , 28 , 30 Regardless, a patient-centered customized roadmap on possible discharge options and expected outcomes will help the interest parties to make complicated medical decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 , 18 , 24 , 25 , 36 For some patients and families, professional supports were critical when caregiving at home was not an option. 11 , 26 , 29 Recently developed telemonitoring service might be a solution to the geographic disparities in access to home-based services. 18 , 27 , 28 , 30 Regardless, a patient-centered customized roadmap on possible discharge options and expected outcomes will help the interest parties to make complicated medical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…and service-specific outcomes (eg, functionality improvement, etc.) will provide additional perspectives in the field, 11 , 26 , 28 , 40 , 41 especially given the fact that post-acute care and hospital readmissions are the 2 major drivers for cost variations overall. 16 , 40 , 42 - 44 Fifth, as with many studies that used administrative data, this study lacks information from patient perspectives.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the general Medicare population, Werner and colleagues have shown that discharge to HHC was associated with higher rates of readmissions, but no impact on mortality 5 . Another national study of Medicare beneficiaries residing in assisted living communities, showed a similar pattern of increased 30‐day readmissions for those receiving HHC, but a lower likelihood of 30‐day mortality 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 Another national study of Medicare beneficiaries residing in assisted living communities, showed a similar pattern of increased 30-day readmissions for those receiving HHC, but a lower likelihood of 30-day mortality. 6 Medicare beneficiaries diagnosed with Alzheimer's disease or related dementia (ADRD) are known to be at an increased risk of hospitalizations and subsequent transitions across care settings. [7][8][9] To date, little is known about PAC transitions among community-dwelling Medicare ADRD population, and even less about how different PAC settings may impact their outcomes.…”
Section: Introductionmentioning
confidence: 99%